Zwitterionic base-stabilized digermadistannacyclobutadiene and tetragermacyclobutadiene - Yeong, Hui-Xian (2014)
The syntheses of a zwitterionic base-stabilized digermadistannacyclobutadiene and tetragermacyclobutadiene supported by amidinates and low-valent germanium amidinate substituents are described. The reaction of the amidinate GeI dimer, [LGe:]2 (1, L=PhC(NtBu)2), with two equivalents of the amidinate tin(II) chloride, [LSnCl] (2), and KC8 in tetrahydrofuran (THF) at room temperature afforded a mixture of the zwitterionic base-stabilized digermadistannacyclobutadiene, [L2Ge2Sn2L′2] (3; L′=LGe:), and the bis(amidinate) tin(II) compound, [L2Sn:] (4). Compound 3 can also be prepared by the reaction of 1 with [LArSnCl] (5, LAr=tBuC(NAr)2, Ar=2,6-iPr2C6H3) in THF at room temperature. Moreover, the reaction of 1 with the “onio-substituent transfer” reagent [4-NMe2-C5H4NSiMe3]OTf (8) in THF and 4-(N,N-dimethylamino)pyridine (DMAP) at room temperature afforded a mixture of the zwitterionic base-stabilized tetragermacyclobutadiene, [L4Ge6] (9), the amidinium triflate, [PhC(NHtBu)2]OTf (10), and Me3SiSiMe3 (11). X-ray structural data and theoretical studies show conclusively that compounds 3 and 9 have a planar and rhombic charge-separated structure. They are also nonaromatic.